Normative Women and Patriarchal Hegemony in Ariyoshi Sawako’s Hanaoka Seishu no Tsuma (1966) - Nina Alia Ariefa; Andhika Pratiwi (Universitas Diponegoro, 2021)
This research examines the depiction of normative women in the Edo period (1603-1868) in the novel entitled Hanaoka Seishu no Tsuma (1966) by Ariyoshi Sawako, a Japanese female writer in the post World War II Showa era. Reflecting on the novel’s normative female characters, it analyzes the silenced voices of women. It will contribute to the discussion on how the normative female figures criticizing the patriarchal hegemony that has not been revealed in the literary canon of the Edo period. This research shows how normative women characters are presented in the text as a feminine strategy to criticize this hegemony. The researchers use feminist criticism theory from Butler’s gender performativity (1990). The study concludes that although normative women characters are commonly represented as men dominating women, those can also be used to criticize the patriarchal hegemony.